2023
DOI: 10.1038/s41467-023-36303-8
|View full text |Cite
|
Sign up to set email alerts
|

New insights in polydopamine formation via surface adsorption

Abstract: Polydopamine is a biomimetic self-adherent polymer, which can be easily deposited on a wide variety of materials. Despite the rapidly increasing interest in polydopamine-based coatings, the polymerization mechanism and the key intermediate species formed during the deposition process are still controversial. Herein, we report a systematic investigation of polydopamine formation on halloysite nanotubes; the negative charge and high surface area of halloysite nanotubes favour the capture of intermediates that ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
64
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(71 citation statements)
references
References 46 publications
7
64
0
Order By: Relevance
“…This is further confirmed by the analysis of N 1s high-resolution spectra of the films since the primary-amine part of the spectrum (N–C) is less significant for the DA/Cu 1:3 sample. A very recent study showed that primary amine contribution decreases with the oxidation time; thus, the decreased level indicates a higher oxidation level . Simultaneously, secondary amine abundance in the DA oxidation products indicates the elevated intramolecular cyclization rate. , Therefore, the effect of the Cu 2+ ions appears in both intermolecular and intramolecular interactions.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This is further confirmed by the analysis of N 1s high-resolution spectra of the films since the primary-amine part of the spectrum (N–C) is less significant for the DA/Cu 1:3 sample. A very recent study showed that primary amine contribution decreases with the oxidation time; thus, the decreased level indicates a higher oxidation level . Simultaneously, secondary amine abundance in the DA oxidation products indicates the elevated intramolecular cyclization rate. , Therefore, the effect of the Cu 2+ ions appears in both intermolecular and intramolecular interactions.…”
Section: Resultsmentioning
confidence: 98%
“…A very recent study showed that primary amine contribution decreases with the oxidation time; thus, the decreased level indicates a higher oxidation level. 55 Simultaneously, secondary amine abundance in the DA oxidation products indicates the elevated intramolecular cyclization rate. 56,57 Therefore, the effect of the Cu 2+ ions appears in both intermolecular and intramolecular interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Codeposition involves the blending of dopamine with another component to form a copolymer that is deposited on the surface of the substrate. The components can be synthetic polymers, biomolecules, small organic molecules, or nanomaterials. Depending on the molecular structure of the component, it forms various interactions with dopamine. The component imparts new properties to the coating on the basis of its characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Although the dopamine monomer consists of catechol and ethylamine, catecholamine is not the only building block of PDA. Dopamine monomer possesses several reactive sites (amine, benzene, or hydroxy), which are electrophiles or nucleophiles, respectively, and thus are prone to create various building blocks such as catecholamine, 5,6-dihydroxy indole (DHI), and dopamine quinone during self-polymerization . Among these components, catecholamine plays a crucial role in adhesion, whereas DHI interferes with adherence. , Although DHI provides a cohesive behavior by promoting intermolecular π–π interaction, cation−π interactions through abundant π-electrons, as well as covalent crosslinking at its 2-position, an abundance of DHIs decreases the adhesion behavior of PDA .…”
Section: Introductionmentioning
confidence: 99%